New, Biocompatible, Chitosan-Gelled Microemulsions Based on Essential Oils and Sucrose Esters as Nanocarriers for Topical Delivery of Fluconazole - Lavinia Vlaia; Ioana Olariu; Ana Maria Muţ; Georgeta Coneac; Vicenţiu Vlaia; Dan Florin Anghel; Monica Elisabeta Maxim; Gabriela Stângă; Amadeus Dobrescu; Maria Suciu; Zoltan Szabadai; Dumitru Lupuleasa (MDPI AG, 2021)
Biocompatible gel microemulsions containing natural origin excipients are promising nanocarrier systems for the safe and effective topical application of hydrophobic drugs, including antifungals. Recently, to improve fluconazole skin permeation, tolerability and therapeutic efficacy, we developed topical biocompatible microemulsions based on cinnamon, oregano or clove essential oil (CIN, ORG or CLV) as the oil phase and sucrose laurate (D1216) or sucrose palmitate (D1616) as surfactants, excipients also possessing intrinsic antifungal activity. To follow up this research, this study aimed to improve the adhesiveness of respective fluconazole microemulsions using chitosan (a biopolymer with intrinsic antifungal activity) as gellator and to evaluate the formulation variables' effect (composition and concentration of essential oil, sucrose ester structure) on the gel microemulsions' (MEGELs) properties. All MEGELs were evaluated for drug content, pH, rheological behavior, viscosity, spreadability, in vitro drug release and skin permeation and antifungal activity. The results showed that formulation variables determined distinctive changes in the MEGELs' properties, which were nevertheless in accordance with official requirements for semisolid preparations. The highest flux and release rate values and large diameters of the fungal growth inhibition zone were produced by formulations MEGEL-FZ-D1616-CIN 10%, MEGEL-FZ-D1216-CIN 10% and MEGEL-FZ-D1616-ORG 10%. In conclusion, these MEGELs were demonstrated to be effective platforms for fluconazole topical delivery.